2015
DOI: 10.1044/2015_aja-15-0005
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Case Studies of Tinnitus Suppression With Mixed Background Stimuli in a Cochlear Implant

Abstract: Purpose Background sounds provided by a wearable sound playback device were mixed with the acoustical input picked up by a cochlear implant speech processor in an attempt to suppress tinnitus. Method First, patients were allowed to listen to several sounds and to select up to 4 sounds that they thought might be effective. These stimuli were programmed to loop continuously in the wearable playback device. Second, subjects were instructed to use 1 backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…A relatively simple pattern generator is sufficient for this treatment option. Moreover, it might be possible that the effectiveness of intracochlear electrical stimulation on tinnitus suppression could be further optimized using a combination of speech processing and the meaningless, but highly controlled, intracochlear electrical stimulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively simple pattern generator is sufficient for this treatment option. Moreover, it might be possible that the effectiveness of intracochlear electrical stimulation on tinnitus suppression could be further optimized using a combination of speech processing and the meaningless, but highly controlled, intracochlear electrical stimulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frequency lowering processing was suggested as an alternative strategy to conventional amplification (Peltier et al, 2012 ). Several studies suggested sound therapy device selection based on the audiogram (from hearing aids, combination instruments and cochlear implants) (Folmer and Carroll, 2006 ; Mazurek et al, 2006 ; Tyler et al, 2015 ; Searchfield, 2016 ). Searchfield ( 2016 ) recommended normal hearing would be fitted with sound generators; high frequency hearing loss with hearing aids; hearing loss encompassing low frequencies with combination instruments; severe-profound hearing loss with cochlear implants.…”
Section: Resultsmentioning
confidence: 99%
“…New approaches are being explored, including cochlear implants for patients with unilateral HL and severe tinnitus, brain stimulation through transcranial magnetic stimulation, and brain stimulation. However, at present, there is no "cure" for tinnitus (Tyler et al, 2015).…”
Section: Tinnitus Treatmentsmentioning
confidence: 99%
“…Several therapeutic approaches, including counselling and behavioural therapy, the provision of hearing aids and cochlear implants (CI), and sound therapy devices can be effective for many people (Kleine Punte, Meeus, & Van de Heyning, 2010;Tyler et al, 2015). Tinnitus treatments are additionally reviewed in Section 4.…”
Section: Introductionmentioning
confidence: 99%